Perception and practice of hand washing in Kuramo Community, Lagos, Nigeria - Ogunsola, Folasade; Balogun, Mobolanle; Aigbefo, Sunny; Oduyebo, Oyinlola; Oladele, Rita; Olufemi, Jumoke; Ajieroh, Victo (International Journal of Infection Control, 2013)
Diarrhoea and respiratory tract infections are common causes of morbidity and mortality among children aged less than five years, particularly in low and middle-income countries and children in the lowest socio economic quintile have higher morbidity and mortality. Contaminated hands are an important mode of transmission from infected persons to susceptible hosts. This cross-sectional baseline assessment was carried out during the months of March – May 2011 in Kuramo beach community, an urban slum on the coastline of Lagos state, Nigeria. The approach was to assess the perception and practice of hand washing, as well as perceptions of the prevalence and aetiology of diarrhoea and upper respiratory infections in the community. Upper respiratory tract infections (URTI) defined as a cough and catarrh was used as an indicator for the transmission of respiratory pathogens. A total of 1000 people from 1000 of an estimated 3000 households were interviewed of these 47.8% were women. The mean age of the respondents was 29.4 years ±10.4 standard deviation. Diarrhoea and URTI were among the most common infections amongst adults and children in Kuramo. There was little knowledge of the role of the hands in the aetiology of diarrhea and URTI.Under-fives were more likely to have had multiple episodes of diarrhoea and URTI in the preceding 3months than older children (p<0.001). Over 75% of respondents knew hand washing required soap but only 46% wash their hands before eating, 3.6% after cleaning a child’s bottom and 0.3% after cleaning a child’s runny nose. This community would benefit from provision of water, and toilets as well as increased training to improve the practice of hand washing.